High‐Pressure High‐Temperature Synthesis of ϵ‐Fe2IrN0.2412. Issue 5 (23rd January 2014) - Guo, Kai; Rau, Dieter; Schnelle, Walter; Burkhardt, Ulrich; Niewa, Rainer; Schwarz, Ulrich
Abstract A high‐pressure high‐temperature synthesis involving initial reaction, nitrogen depletion and annealing yields a new ϵ‐type iron iridium nitride. Energy dispersive X‐ray spectroscopy of metallographic samples evidence a main phase having a molar metal ratio of Fe:Ir = 2:1 within experimental error. Chemical analyses and thermogravimetric measurements quantify the nitrogen content to 1.07 wt % (x = 0.24) and 1.2 wt % (x = 0.27), respectively. Above 750 K, the phase Fe2IrN0.24 decomposes into solid solutions ϵ‐Fe(Ir) and γ‐Fe(Ir) involving the release of N2 at ambient pressure. Magnetic susceptibility data suggest long‐range antiferromagnetic ordering at TN = 27 K.